Detection of CTX-M-Type Extended Spectrum Beta-Lactamase Producing Salmonella Typhimurium in Commercial Poultry Farms in Copperbelt Province, Zambia - Naomi Kaonga; Abubakar Hoza; Athumani Lupindu; Bernard Hangombe (German Journal of Veterinary Research)
In Zambia, poultry is a rapid increasing sector contributing 4.8% of the Agricultural Gross Domestic Product (GDP), thus providing a significant income generating activity. Worldwide, poultry is a major reservoir of Salmonella with increasing incidence of extended spectrum beta-lactamase (ESBL) producing strains. ESBLs are enzymes produced by bacteria and are capable of inactivating a wide range of beta-lactam antibiotics. Salmonella enterica serovars Enteritidis and Typhimurium are the most important foodborne serotypes in many countries infecting both humans and animals and are transmitted to humans through the food supply chain. CTX-M ESBLs have been described in Salmonella Typhimurium isolates with resistant genes located on transferable plasmids. This study aimed to detect S. Typhimurium, their antimicrobial resistance and CTX-M-type ESBL Producing strains in commercial poultry farms in Copperbelt Province, Zambia. Five districts were considered for this study where one poultry farm per district was randomly selected for sampling. An overall number of 384 faecal samples were analysed using microbiological and molecular methods. S. Typhimurium was detected at 17.7% (CI: 14.2%-21.8%) in commercial poultry farms in Copperbelt Province of which 12.8% (CI: 9.8%-16.5%) were found harboring the CTX-M-Type ESBL genes. S. Typhimurium isolates showed 88.2% resistance to at least one antimicrobial compounds. All the isolates showed 100% resistance to tetracycline followed by ampicillin and amoxicillin at 91.2%. These isolates also showed 58.8% resistance to cefotaxime and 54.4% to ceftazidime. Detection of CTX-M ESBL producing Salmonella Typhimurium suggests that there is contamination of chicken food chain at farm level and call for public health protection measures.